Answer

Verified

406.5k+ views

Hint: Firstly assume the digits to be $a,ar,a{{r}^{2}}$after that you can apply the conditions accordingly. Use the formula of A.P. given by If a,b,c are in A.P. then , $b=\dfrac{a+c}{2}$ so that you will get a simpler equation. After that use the last condition and solve it to find ‘r’ and on further solving you will get ‘a’.

Complete step-by-step answer:

To solve the given problem we have to assume the digits and as they are in G.P. therefore we have the standard consecutive numbers to be assumed which are given by,

Therefore the three consecutive digits of the number are given by,

$a,ar,a{{r}^{2}}$ …………………………………………… (1)

Where, ‘a’ is the first term and ’r’ is the common ratio of G.P.

$100a+10ar+a{{r}^{2}}$

If we take ‘a’ as common we will get,

$a\left( 100+10r+{{r}^{2}} \right)$ …………………………….. (2)

As given in the problem if the middle digit is increased by 2 then it will form an A.P.

Therefore,

$a,ar+2,a{{r}^{2}}$ form an A.P.

To proceed further we should know the formula given below,

Formula:

If a,b,c are in A.P. then , $b=\dfrac{a+c}{2}$.

By using the formula we can write,

$ar+2=\dfrac{a+a{{r}^{2}}}{2}$

$\therefore 2\left( ar+2 \right)=a+a{{r}^{2}}$

$\therefore 2ar+4=a+a{{r}^{2}}$

$\therefore 4=a{{r}^{2}}-2ar+a$

By taking ‘a’ common we will get,

$\therefore 4=a\left( {{r}^{2}}-2r+1 \right)$

To proceed further in the solution we should know the formula given below,

Formula:

${{\left( a-b \right)}^{2}}={{a}^{2}}-2ab+{{b}^{2}}$

By using the above formula we can write,

$\therefore 4=a{{\left( r-1 \right)}^{2}}$

By rearranging the above equation we will get,

$\therefore a{{\left( r-1 \right)}^{2}}=4$ …………………………………….. (3)

To proceed further we should write the number in reverse order therefore, from equation (1) we can write the number in reverse order as,

$100a{{r}^{2}}+10ar+a$

By taking ‘a’ common we will get,

$a\left( 100{{r}^{2}}+10r+1 \right)$ ………………………………. (4)

Now, by using the second condition given in the problem and using equation (2) and equation (4), we will get,

$a\left( 100+10r+{{r}^{2}} \right)-792=a\left( 100{{r}^{2}}+10r+1 \right)$

By taking 792 on the right side of the equation and reverse order number on the left hand side of the equation we will get

$a\left( 100+10r+{{r}^{2}} \right)-a\left( 100{{r}^{2}}+10r+1 \right)=792$

By taking ‘a’ common we will get,

$a\left[ \left( 100+10r+{{r}^{2}} \right)-\left( 100{{r}^{2}}+10r+1 \right) \right]=792$

By opening the parenthesis we will get,

$\therefore a\left[ 100+10r+{{r}^{2}}-100{{r}^{2}}-10r-1 \right]=792$

$\therefore a\left[ 100+{{r}^{2}}-100{{r}^{2}}-1 \right]=792$

$\therefore a\left[ 99-99{{r}^{2}} \right]=792$

By taking 99 common we will get,

$\therefore 99a\left[ 1-{{r}^{2}} \right]=792$

$\therefore a\left[ 1-{{r}^{2}} \right]=\dfrac{792}{99}$

Dividing by 9 to numerator and denominator on the right hand side of the equation we will get,

$\therefore a\left[ 1-{{r}^{2}} \right]=\dfrac{88}{11}$

$\therefore a\left[ 1-{{r}^{2}} \right]=8$

Dividing above equation by equation (3) we will get,

$\therefore \dfrac{a\left( 1-{{r}^{2}} \right)}{a{{\left( r-1 \right)}^{2}}}=\dfrac{8}{4}$

$\therefore \dfrac{\left( 1-{{r}^{2}} \right)}{{{\left( r-1 \right)}^{2}}}=2$

By taking -1 common from denominator of left hand side of the equation we will get,

$\therefore \dfrac{\left( 1-{{r}^{2}} \right)}{{{\left[ -1\left( 1-r \right) \right]}^{2}}}=2$

$\therefore \dfrac{\left( 1-{{r}^{2}} \right)}{{{\left( 1-r \right)}^{2}}}=2$

To proceed further we should know the formula given below,

Formula:

${{a}^{2}}-{{b}^{2}}=\left( a+b \right)\times \left( a-b \right)$

By using above formula we will get,

$\therefore \dfrac{\left( 1-r \right)\left( 1+r \right)}{{{\left( 1-r \right)}^{2}}}=2$

$\therefore \dfrac{\left( 1+r \right)}{\left( 1-r \right)}=2$

$\therefore \left( 1+r \right)=2\left( 1-r \right)$

$\therefore \left( 1+r \right)=2-2r$

$\therefore r+2r=2-1$

$\therefore 3r=1$

$\therefore r=\dfrac{1}{3}$ …………………………………………… (5)

By substituting the value of equation (5) in equation (3) we will get,

$\therefore a{{\left( \dfrac{1}{3}-1 \right)}^{2}}=4$

$\therefore a{{\left( \dfrac{1-3}{3} \right)}^{2}}=4$

$\therefore a{{\left( \dfrac{-2}{3} \right)}^{2}}=4$

$\therefore a\times \dfrac{4}{9}=4$

$\therefore a=4\times \dfrac{9}{4}$

$\therefore a=9$ …………………………………………. (6)

Now if we put the values of equation (5) and equation (6) in equation (2) we will get,

$\therefore $The required number $=a\left( 100+10r+{{r}^{2}} \right)$

$\therefore $The required number $=9\times \left[ 100+10\times \left( \dfrac{1}{3} \right)+{{\left( \dfrac{1}{3} \right)}^{2}} \right]$

$\therefore $The required number $=9\times 100+9\times 10\times \left( \dfrac{1}{3} \right)+9\times {{\left( \dfrac{1}{3} \right)}^{2}}$

$\therefore $The required number $=900+3\times 10\ +9\times \dfrac{1}{9}$

$\therefore $The required number $=900+30+1$

$\therefore $The required number $=931$

Therefore the number which satisfies all the conditions given in the problem is 931.

Note: Don’t assume the digits to be $\dfrac{a}{r},a,ar$, as it will become very much difficult for calculation, it will be better if we use the digits as$a,ar,a{{r}^{2}}$, as it will save your time in solving which is beneficial in competitive exams.

Complete step-by-step answer:

To solve the given problem we have to assume the digits and as they are in G.P. therefore we have the standard consecutive numbers to be assumed which are given by,

Therefore the three consecutive digits of the number are given by,

$a,ar,a{{r}^{2}}$ …………………………………………… (1)

Where, ‘a’ is the first term and ’r’ is the common ratio of G.P.

$100a+10ar+a{{r}^{2}}$

If we take ‘a’ as common we will get,

$a\left( 100+10r+{{r}^{2}} \right)$ …………………………….. (2)

As given in the problem if the middle digit is increased by 2 then it will form an A.P.

Therefore,

$a,ar+2,a{{r}^{2}}$ form an A.P.

To proceed further we should know the formula given below,

Formula:

If a,b,c are in A.P. then , $b=\dfrac{a+c}{2}$.

By using the formula we can write,

$ar+2=\dfrac{a+a{{r}^{2}}}{2}$

$\therefore 2\left( ar+2 \right)=a+a{{r}^{2}}$

$\therefore 2ar+4=a+a{{r}^{2}}$

$\therefore 4=a{{r}^{2}}-2ar+a$

By taking ‘a’ common we will get,

$\therefore 4=a\left( {{r}^{2}}-2r+1 \right)$

To proceed further in the solution we should know the formula given below,

Formula:

${{\left( a-b \right)}^{2}}={{a}^{2}}-2ab+{{b}^{2}}$

By using the above formula we can write,

$\therefore 4=a{{\left( r-1 \right)}^{2}}$

By rearranging the above equation we will get,

$\therefore a{{\left( r-1 \right)}^{2}}=4$ …………………………………….. (3)

To proceed further we should write the number in reverse order therefore, from equation (1) we can write the number in reverse order as,

$100a{{r}^{2}}+10ar+a$

By taking ‘a’ common we will get,

$a\left( 100{{r}^{2}}+10r+1 \right)$ ………………………………. (4)

Now, by using the second condition given in the problem and using equation (2) and equation (4), we will get,

$a\left( 100+10r+{{r}^{2}} \right)-792=a\left( 100{{r}^{2}}+10r+1 \right)$

By taking 792 on the right side of the equation and reverse order number on the left hand side of the equation we will get

$a\left( 100+10r+{{r}^{2}} \right)-a\left( 100{{r}^{2}}+10r+1 \right)=792$

By taking ‘a’ common we will get,

$a\left[ \left( 100+10r+{{r}^{2}} \right)-\left( 100{{r}^{2}}+10r+1 \right) \right]=792$

By opening the parenthesis we will get,

$\therefore a\left[ 100+10r+{{r}^{2}}-100{{r}^{2}}-10r-1 \right]=792$

$\therefore a\left[ 100+{{r}^{2}}-100{{r}^{2}}-1 \right]=792$

$\therefore a\left[ 99-99{{r}^{2}} \right]=792$

By taking 99 common we will get,

$\therefore 99a\left[ 1-{{r}^{2}} \right]=792$

$\therefore a\left[ 1-{{r}^{2}} \right]=\dfrac{792}{99}$

Dividing by 9 to numerator and denominator on the right hand side of the equation we will get,

$\therefore a\left[ 1-{{r}^{2}} \right]=\dfrac{88}{11}$

$\therefore a\left[ 1-{{r}^{2}} \right]=8$

Dividing above equation by equation (3) we will get,

$\therefore \dfrac{a\left( 1-{{r}^{2}} \right)}{a{{\left( r-1 \right)}^{2}}}=\dfrac{8}{4}$

$\therefore \dfrac{\left( 1-{{r}^{2}} \right)}{{{\left( r-1 \right)}^{2}}}=2$

By taking -1 common from denominator of left hand side of the equation we will get,

$\therefore \dfrac{\left( 1-{{r}^{2}} \right)}{{{\left[ -1\left( 1-r \right) \right]}^{2}}}=2$

$\therefore \dfrac{\left( 1-{{r}^{2}} \right)}{{{\left( 1-r \right)}^{2}}}=2$

To proceed further we should know the formula given below,

Formula:

${{a}^{2}}-{{b}^{2}}=\left( a+b \right)\times \left( a-b \right)$

By using above formula we will get,

$\therefore \dfrac{\left( 1-r \right)\left( 1+r \right)}{{{\left( 1-r \right)}^{2}}}=2$

$\therefore \dfrac{\left( 1+r \right)}{\left( 1-r \right)}=2$

$\therefore \left( 1+r \right)=2\left( 1-r \right)$

$\therefore \left( 1+r \right)=2-2r$

$\therefore r+2r=2-1$

$\therefore 3r=1$

$\therefore r=\dfrac{1}{3}$ …………………………………………… (5)

By substituting the value of equation (5) in equation (3) we will get,

$\therefore a{{\left( \dfrac{1}{3}-1 \right)}^{2}}=4$

$\therefore a{{\left( \dfrac{1-3}{3} \right)}^{2}}=4$

$\therefore a{{\left( \dfrac{-2}{3} \right)}^{2}}=4$

$\therefore a\times \dfrac{4}{9}=4$

$\therefore a=4\times \dfrac{9}{4}$

$\therefore a=9$ …………………………………………. (6)

Now if we put the values of equation (5) and equation (6) in equation (2) we will get,

$\therefore $The required number $=a\left( 100+10r+{{r}^{2}} \right)$

$\therefore $The required number $=9\times \left[ 100+10\times \left( \dfrac{1}{3} \right)+{{\left( \dfrac{1}{3} \right)}^{2}} \right]$

$\therefore $The required number $=9\times 100+9\times 10\times \left( \dfrac{1}{3} \right)+9\times {{\left( \dfrac{1}{3} \right)}^{2}}$

$\therefore $The required number $=900+3\times 10\ +9\times \dfrac{1}{9}$

$\therefore $The required number $=900+30+1$

$\therefore $The required number $=931$

Therefore the number which satisfies all the conditions given in the problem is 931.

Note: Don’t assume the digits to be $\dfrac{a}{r},a,ar$, as it will become very much difficult for calculation, it will be better if we use the digits as$a,ar,a{{r}^{2}}$, as it will save your time in solving which is beneficial in competitive exams.

Recently Updated Pages

Three beakers labelled as A B and C each containing 25 mL of water were taken A small amount of NaOH anhydrous CuSO4 and NaCl were added to the beakers A B and C respectively It was observed that there was an increase in the temperature of the solutions contained in beakers A and B whereas in case of beaker C the temperature of the solution falls Which one of the following statements isarecorrect i In beakers A and B exothermic process has occurred ii In beakers A and B endothermic process has occurred iii In beaker C exothermic process has occurred iv In beaker C endothermic process has occurred

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

Define absolute refractive index of a medium

Find out what do the algal bloom and redtides sign class 10 biology CBSE

Prove that the function fleft x right xn is continuous class 12 maths CBSE

Find the values of other five trigonometric functions class 10 maths CBSE

Trending doubts

How do you solve x2 11x + 28 0 using the quadratic class 10 maths CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Write a book review which you have recently read in class 8 english CBSE

Difference Between Plant Cell and Animal Cell

Describe the poetic devices used in the poem Aunt Jennifers class 12 english CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

State the laws of reflection of light

What I want should not be confused with total inactivity class 12 english CBSE